Excitation and control of plasma wakefields by multiple laser pulses - Cowley, J; Thornton, C; Arran, C; Shalloo, RJ; Corner, L; Cheung, G; Gregory, CD; Mangles, SPD; Matlis, NH; Symes, DR; Walczak, R; Hooker, SM (American Physical Society, 2017)
We demonstrate experimentally the resonant excitation of plasma waves by trains of laser pulses. We also take an important first step to achieving an energy recovery plasma accelerator by showing that a plasma wave can be damped by an out-of-resonance trailing laser pulse. The measured laser wakefields are found to be in excellent agreement with analytical and numerical models of wakefield excitation in the linear regime. Our results indicate a promising direction for achieving highly controlled, GeV-scale laser-plasma accelerators operating at multikilohertz repetition rates.